Original Articles: Non–Small Cell Lung Cancer - Nodal Upstaging Is More Common with Thoracotomy than with VATS During Lobectomy for Early-Stage Lung Cancer: An Analysis from the National Cancer Data Base. Issue 2 (February 2016) - Medbery, Rachel L.; Gillespie, Theresa W.; Liu, Yuan; Nickleach, Dana C.; Lipscomb, Joseph; Sancheti, Manu S.; Pickens, Allan; Force, Seth D.; Fernandez, Felix G.
ABSTRACT: : Introduction: : Questions remain regarding differences in nodal evaluation and upstaging between thoracotomy (open) and video‐assisted thoracic surgery (VATS) approaches to lobectomy for early‐stage lung cancer. Potential differences in nodal staging based on operative approach remain the final significant barrier to widespread adoption of VATS lobectomy. The current study examines differences in nodal staging between open and VATS lobectomy. Methods: : The National Cancer Data Base was queried for patients with clinical stage T2N0M0 or lower lung cancer who underwent lobectomy in 2010–2011. Propensity score matching was performed to compare the rate of nodal upstaging in VATS with that in open approaches. Additional subgroup analysis was performed to assess whether rates of upstaging differed by specific clinical setting. Results: : A total of 16, 983 lobectomies were analyzed; 4935 (29.1%) were performed using VATS. Nodal upstaging was more frequent in the open group (12.8% versus 10.3%; p < 0.001). In 4437 matched pairs, nodal upstaging remained more common for open approaches. For a subgroup of patients who had seven lymph or more nodes examined, propensity matching revealed that nodal upstaging remained more common after an open approach than after VATS (14.0% versus 12.1%; p = 0.03). For patients who were treated in an academic/research facility, however, the difference in nodal upstaging between an open and VATS approach was no longer significant (12.2% versus 10.5%, p = 0.08). Conclusions: : For early‐stage lung cancer, nodal upstaging was observed more frequently with thoracotomy than with VATS. However, nodal upstaging appears to be affected by facility type, which may be a surrogate for expertise in minimally invasive surgical procedures.